AAIT: A novel prognostic model for HIV-negative patients with cryptococcal meningoencephalitis New Scoring Model for Non-HIV Patients with CM. (10th December 2020) - Cai, Qun; Wang, Hao; Ruan, Sihan; Zhu, Mingyan; Duan, Jinnan; Sun, Shanshan; Sheng, Jifang
Abstract: Cryptococcal meningitis (CM) is a common opportunistic infection in HIV-negative patients, with mortality rates as high as those in the HIV-negative population. This requires accurate initial clinical decision-making, warranting the development of a prognostic score. Two groups of patients were investigated separately to develop a novel prognostic model (AAIT) for HIV-negative patients with CM. A retrospective analysis of 201 HIV-negative patients with CM was conducted to develop the CM prognostic score. In addition, the CM cohort (n = 21) was recruited longitudinally to verify the new prognostic score. Meanwhile, the association between the prognostic score and 1-year mortality of CM was expounded. AAIT (age, albumin, combined bacterial infection, and total triiodothyronine) is a novel prognostic score based on age, albumin level, combined bacterial infection, and total triiodothyronine (TT3) level, which were significantly higher in nonsurvivors than in survivors (0.68 [−0.70 to 1.55] vs − 1.72 [−3.75 to −0.73], P < .00). Regarding the AAIT-predicted 1-year mortality, the area under the receiver operating characteristic curve (AUROC) value was 0.857, whereas it was 0.965 for the validation cohort. In the induction period, different treatment options did not seem to significantly improve the 1-year survival rate. AAIT is a straightforward and clear prognostic score that can add value to predict the outcomes in HIV-negative patients with CM. In addition, controlling infection and increasing the albumin and TT3 levels may help improve clinical outcomes in HIV-negative patients with CM. Lay Summary: AAIT (age, albumin, combined bacterial infection, and total triiodothyronine) is a straightforward and clear prognostic score that can add value to predict the outcomes HIV-negative patients with CM.